2014
DOI: 10.1128/aem.03710-13
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Ethanol Yield and Improvement of Glycerol Formation by Adaptive Evolution of the Wine Yeast Saccharomyces cerevisiae under Hyperosmotic Conditions

Abstract: There is a strong demand from the wine industry for methodologies to reduce the alcohol content of wine without compromising wine's sensory characteristics. We assessed the potential of adaptive laboratory evolution strategies under hyperosmotic stress for generation of Saccharomyces cerevisiae wine yeast strains with enhanced glycerol and reduced ethanol yields. Experimental evolution on KCl resulted, after 200 generations, in strains that had higher glycerol and lower ethanol production than the ancestral st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
111
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 46 publications
(63 reference statements)
7
111
0
1
Order By: Relevance
“…On the other hand, an atractive option would be to develop engineered wine yeast with reduced ethanol yield. So far, one of the most promising strategies is to redirect the metabolic lux toward an increased production of glycerol instead ethanol [2,35]. However, this strategy has shown some unwanted efects like an overproduction of undesirable compounds from an organoleptic point of view [1].…”
Section: Biotechnological Approaches To Reduce the Alcohol Content Inmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, an atractive option would be to develop engineered wine yeast with reduced ethanol yield. So far, one of the most promising strategies is to redirect the metabolic lux toward an increased production of glycerol instead ethanol [2,35]. However, this strategy has shown some unwanted efects like an overproduction of undesirable compounds from an organoleptic point of view [1].…”
Section: Biotechnological Approaches To Reduce the Alcohol Content Inmentioning
confidence: 99%
“…This property has been used in recent years to modify the natural properties of yeasts by conducting adaptive laboratory evolution (ALE) experiments [2]. This approach mimics the natural evolution, by environmental or metabolic constraints, with the main purpose of obtaining improve yeast strains for several biotechnological applications and, of course, in winemaking processes [37][38][39][40].…”
Section: Biotechnological Approaches To Reduce the Alcohol Content Inmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, using genetic engineering [20,43,44] and non-GM techniques, [45] such as classical breeding (hybridization), adaptive laboratory evolution, and mutagenesis, several non-GM and GM wine strains have been developed with increased robustness, fermentation performance, health-related properties, and/or sensory attributes. Examples include strains that produce wines with lower alcohol levels; [46][47][48][49][50][51][52][53][54][55] mutants that limit the production of unwanted hydrogen-sulfide off-flavors and volatile acidy; [56][57][58] and strains that produce desirable esters, [59,60] terpenes, [61] and thiols ( Figure 18). [62][63][64][65][66][67][68][69][70] Efforts are also underway to express the a-guaiene-2-oxidase from grapevine in S. cerevisiae, thereby equipping wine yeast to transform grapederived a-guaiene to the sought-after spicy aroma compound of Shiraz wine, rotundone.…”
Section: Bioengineered Yeast Put Synthetic Dna To Work In Industrymentioning
confidence: 99%
“…Several strategies that use genetically modified (GM) yeasts have been proposed for the production low-alcohol wine. Recently, Tilloy and co-workers [3] using evolution-based strategies together with breeding strategy showed that evolved or hybrid strains produced an ethanol reduction of 0.6-1.3% (vol/vol) in comparison with ancestral strain.…”
Section: Introductionmentioning
confidence: 99%